From Proving Perfection to Seeking Support: The Lived Experiences of Adoptive Parents in Alberta - McKirdy, Gillian C.; Roughley, Robert A.; McKirdy, Scott A. (Canadian Journal of Counselling and Psychotherapy, 2019)
The purpose of this phenomenological study on the lived experiences of 14 adoptive parents in Alberta is to gain deeper insights into how parents (a) experience the process of adoption, and (b) seek support and receive support services. The intent is also to increase understanding and determine if any changes to current practices are needed. This study uncovers how some adoptive parents experience the process as traumatic, while others feel unsupported. The need to substantiate oneself as a perfect parent to get approved for adoption, and then request support for adoption after placement, can be both isolating and challenging for parents. Recommendations on adoption processes are discussed, as well as implications for the field of counselling.